From waste to Wealth: Unveiling drivers, moderators, and strategic pathways for circular economy adoption and investment in Vietnam's FDI sector - Bui Huy Nhuong; Dinh Duc Truong; Bui Thi Hoang Lan; Bui Huy Quang; Duong Duc Tam (Environmental and Sustainability Indicators, 2025)
The transition from linear economy to circular economy (CE) has become a trend in the world for sustainable development, including Vietnam, a developing country with strong economic growth and integration. The objective of this study is to explore and analyze the strategic drivers of CE adoption behavior and willingness to invest in CE of FDI enterprises in Vietnam. At the same time, the study also analyzes the moderating role of government support in the relationship between these drivers and adoption and investment in CE. The study combines three theories including Institutional Theory, Dynamic Capability Theory and Resource Based View Theory to build an empirical model. Data were collected through questionnaires and direct surveys of 378 FDI enterprises, and then analyzed with techniques such as Cronbach'Alpha analysis, confirmatory factor analysis (CFA), and structural equation modeling (SEM). The research results show that the adoption of CE in FDI enterprises is influenced by external environmental factors (such as coercive pressure and norms), internal factors (such as leadership awareness and commitment, management capacity, technological innovation capability, financial efficiency) and dynamic capability factors (especially the ability to sense market opportunities and grasp technology investment). Notably, the Government's support not only directly promotes adoption but also plays an important regulatory role, increasing the impact of coercive pressure and the ability to sense opportunities on CE adoption behavior, while strengthening the relationship between adoption and investment willingness. From there, the study suggests important management implications: the Government needs to continue to improve the legal framework and incentive policies to enhance motivation and reduce barriers for enterprises; FDI enterprises should focus on strengthening innovation capacity and long-term strategy on CE; meanwhile, stakeholders need to build an ecosystem that supports knowledge, technology and finance to drive sustainable transformation across the industry.